2010
DOI: 10.4028/www.scientific.net/amr.150-151.1504
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Thermal Property of Linear Chloromethylated Polystyrene

Abstract: Polystyrene (PS) was synthesized by emulsion polymerization. 1,4-bis(chloromethoxy)butane (BCMB) was synthesized using 1,4-butanediol, formaldehyde and phosphorus trichloride as raw material. The linear poly(p-chloromethyl styrene) (PS-Meyl-Cl) was prepared high effectively using BCMB and anhydrous aluminium trichloride as the chloromethylation reagent and catalyst, respectively. In this method, carcinogenic compound (chloromethyl ether etc.) was avoided. The resultant polymers were characterized by gel permea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Thermal degradation of chloromethylated PS (7), used as reference, occurs in two stages, which is in accordance to other data published by Zhao et al [21]. These authors found also two steps of thermal decomposition for this polymer; moreover, they proved that its thermal stability decreased with increasing content of chloromethyl groups.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Thermal degradation of chloromethylated PS (7), used as reference, occurs in two stages, which is in accordance to other data published by Zhao et al [21]. These authors found also two steps of thermal decomposition for this polymer; moreover, they proved that its thermal stability decreased with increasing content of chloromethyl groups.…”
Section: Resultssupporting
confidence: 80%
“…It was found that in the case of other para-substituted polystyrenes also monomer is usually the main degradation product, however, the composition of other minor formed compounds is very complex [21][22][23][24][25]. The course of thermal degradation is dependent on the kind and amount of substituents.…”
Section: Discussion Of Mechanism Of Thermal Degradation Of New Poly (mentioning
confidence: 99%
“…Figure 2 represents the FT-IR spectra of the prepared resins and CMPS. In the CMPS spectra, the strong absorption peak at 673 cm −1 indicated that the CMPS contained quite a few C-Cl groups [31]. However, after amination reaction, this band gradually weakened or disappeared with the increase of the functional group densities of resins, which suggested that the chlorine methyl was involved in Figure 2 represents the FT-IR spectra of the prepared resins and CMPS.…”
Section: Characterization Of Different Functional Group Density Resinsmentioning
confidence: 98%
“…However, after amination reaction, this band gradually weakened or disappeared with the increase of the functional group densities of resins, which suggested that the chlorine methyl was involved in Figure 2 represents the FT-IR spectra of the prepared resins and CMPS. In the CMPS spectra, the strong absorption peak at 673 cm −1 indicated that the CMPS contained quite a few C-Cl groups [31]. However, after amination reaction, this band gradually weakened or disappeared with the increase of the functional group densities of resins, which suggested that the chlorine methyl was involved in the reaction.…”
Section: Characterization Of Different Functional Group Density Resinsmentioning
confidence: 99%